(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The human being is closely related to the flora and fauna of its environment, being dependent on it to the performance of various activities. The use of the qualities of the surrounding species, has allowed to grant an identity, creating a cultural genesis of the use of local resources. The Salinas de Nahualapa indigenous community; has several ethnoecological, ethnobotanical and ethnozoological resources. This research has the purpose of describing the ethnobiological knowledge of this community. A total of 41 interviews were made to people between the ages of 17 and 98, accompanied of observation in- situ for the taxonomic identification of species, audio recording and photographs of respondents and specimens. The ethnoecological resources that the community has are mostly aquatic, these are: beaches, hot springs, rivers and mangroves. In the ethnobotanical characterization, 68 species belonging to 60 genera and 36 botanical families were registered. Of which 48 are introduced and 20 are native. These are divided into multiple uses, the main ones are: medicinal and nutritional. The most commonly used parts of the plants are: fruit (23), leaf (21), seed (10), stem (8), root (8), flower (3), bulb (2). The most frequent preparation modes are: infusion (23), spread (8) and soda (2). The ethnozoological collection consists of 72 species, with native (55) and introduced (17) status belonging to 33 orders, 58 families, 71 genera. The uses are: food, domestic, pest, poisonous, biological, medicinal and transport controller.